1997 Philippine yearbook. - Philippines. National Statistics Office (Manila National Statistics Office, 1997)
Purpose: "A complete update of the 1995 edition, which seeks to provide data users from both the government and private sectors, students, researchers, and the general public with vital information about the Philippines."
Contents: History of the Philippines. Philippine government. Philippine society and environment. Special feature: a study of poor families in the Philippines. Appendices. Index. The covers.
This yearbook provides information regarding government and private sectors, students, researchers and the general public with vital information about the Philippines.
A complete update of the 1995 edition, this seeks to provide data users from both government and private sectors, students, researchers, and the general public, with vital information about the Philippines. An addendum contains the latest data available as of printing, such as updates on foreign trade, labor force, consumer price index, and other statistics. A Special Feature presents a study of the poor from a countrywide perspective down to the city level to compare characteristics of the poor in one area of the Philippines to another, which might aid in designing a redressal program at the national level to alleviate their plight.
Supersedes: Yearbook of Philippine Statistics and Philippine statistics yearbook.
Keywords: Philippines -- Description and travel; Philippines -- Statistics